Effects of high oleic acid peanuts on mice’s liver and adipose tissue metabolic parameters and gut microbiota composition - Anavi-Cohen, Sarit; Tsybina-Shimshilashvili, Nina; Zandani, Gil; Hovav, Ran; Sela, Noa; Nyska, Abraham; Madar, Zecharia (Frontiers in Nutrition, 2023)
This study aimed to investigate the effects of two types of peanuts, regular Hanoch (HN) and a new high-oleic cultivar, Hanoch-Oleic (HO), on metabolic parameters and gut microbiota composition. Male C57BL/6 mice were fed with a normal diet (ND) or ND supplemented with HN (NDh) or HO (NDo). Following 18 weeks of diet regimen, the NDo group exhibited reduced body weight and peri-gonadal adipose-to-body weight ratio, paralleled to lesser food consumption. Although blood levels of total cholesterol, HDL-cholesterol, free fatty acids, and liver enzyme levels did not differ between groups, decreased insulin sensitivity was found in the NDh group. Within adipose tissue, the expression of lipolytic and lipogenic enzymes was higher, while those related to lipid oxidation were lower in the NDh group compared to the NDo group. Additionally, HO peanuts consumption promoted the establishment of a healthy microbiota, with an enhanced abundance of Bifidobacterium, Lactobacillus, and Coprococcus genera. In conclusion, the inclusion of the HO peanut cultivar, rather than the conventional peanut cultivar, in a balanced diet was related to better metabolic outcomes and was linked to a favorable microbiota profile.